The Role of the Pastoral Practitioner in Health Outcomes and Wellbeing During Acute Illness: Exploring the Patient Experience of a Pastoral Visit - Brown, Janie (Journal of pastoral care & counseling, 2017)
The role of the pastoral practitioner is embedded in many health care services and organizations. Despite this, there is little evidence to describe the impact of this role on patient outcomes, in particular how visits by a pastoral practitioner influence patient healing and recovery. This paper describes a small study that explored the patient experience of pastoral practitioner visits in an acute care facility.